1994
DOI: 10.1159/000282624
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effects of High Energy Shock Wave Alone and Combined with Anticancer Drugs on Human Bladder Cancer Cells

Abstract: We investigated the in vitro effects of high energy shock wave alone or combined with anticancer drug treatment on an established human bladder cancer cell line, KK-47 cells. Exposure of the cell suspensions to 500-2,500 shock waves, generated with the EDAP lithotriptor LTO1 resulted in reduced cell viability with an increasing number of shock doses. DNA flow cytometric analysis revealed a marginal effect on the G2+M and S phases of the cell cycle. When shock wave-treated cells were exposed to mitomycin C, cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The in vitro effects of shock waves are due to a suppression of cell proliferation correlated with an apoptotic cell death process; moreover, HESW treatment has been shown to cause a transient increase in cell membrane permeability by opening micropores (such as electroporation), allowing higher intracellular drug concentration (12-16). This effect has been shown as being capable of increasing the cytotoxicity of various chemotherapeutic agents on different tumour types, allowing treatments with lower doses of drugs in vitro (17)(18)(19), in vivo in animal models (12,20) and in one patient with prostate cancer (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro effects of shock waves are due to a suppression of cell proliferation correlated with an apoptotic cell death process; moreover, HESW treatment has been shown to cause a transient increase in cell membrane permeability by opening micropores (such as electroporation), allowing higher intracellular drug concentration (12-16). This effect has been shown as being capable of increasing the cytotoxicity of various chemotherapeutic agents on different tumour types, allowing treatments with lower doses of drugs in vitro (17)(18)(19), in vivo in animal models (12,20) and in one patient with prostate cancer (21).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro effects of shock waves are due to a suppression of cell proliferation correlated with an apoptotic cell death process; moreover, HESW treatment has been shown to cause a transient increase in cell membrane permeability by opening micropores (such as electroporation), allowing higher intracellular drug concentration (12-16). This effect has been shown as being capable of increasing the cytotoxicity of various chemotherapeutic agents on different tumour types, allowing treatments with lower doses of drugs in vitro (17)(18)(19), in vivo in animal models (12,20) and in one patient with prostate cancer (21).This evidence led us to study the effects of HESW on OS cell lines and how to enhance cytotoxicity with a combined therapy with HESW and doxorubicin (DOXO) or methotrexate (MTX). These cytotoxic agents have been chosen since their well-known activity against OS and their routine use in clinical protocols for the treatment of OS patients (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Toxicity is characterized by the loss of plasma membrane integrity and release of the cytoplasmic enzyme LDH (Wyllie et al, 1980). The release of LDH into the culture supernatant has been used as an indicator of cell death (Phillips et al, 1996), and human bladder cancer cells have been shown to release LDH when treated with cytotoxic agents (Rahman, 1994). As shown in Figure 4, MCC is not cytotoxic towards HT-1376 cells, as determined by the release of LDH into the culture supernatant.…”
Section: Inhibition Of Cancer Cell Proliferation By MCCmentioning
confidence: 99%
“…[1][2][3] The apparent feasibility of exposing a spatially limited region of the body to a potentially destructive form of mechanical energy has led to the idea of applying shock waves in tumor therapy. 4) Previous results have not necessarily been promising, in cases of shock wave therapy alone, [4][5][6][7][8] or in combination with various anti-cancer agents, for example, cisplatinum, [9][10][11][12][13] mitomycin C (MMC), 12,13) actinomycin D, 12) methotrexete 13) and adriamycin (ADR). 11,13,14) However, we have reported that the combination of focused shock waves and bleomycin (BLM) reduced the IC 50 of BLM to 1/10 000-1/100 000 in various human cancer cell lines, when compared to BLM alone.…”
mentioning
confidence: 99%